2019
DOI: 10.1016/j.ssmph.2019.100434
|View full text |Cite
|
Sign up to set email alerts
|

The role of adult socioeconomic and relational reserves regarding the effect of childhood misfortune on late-life depressive symptoms

Abstract: Background Childhood misfortune is associated with late-life depressive symptoms, but it remains an open question whether adult socioeconomic and relational reserves could reduce the association between childhood misfortune and late-life depressive symptoms. Methods Using the Survey of Health, Ageing and Retirement in Europe (SHARE), data from 8'357 individuals (35'260 observations) aged 50–96 years and living in 11 European countries were used to examine associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
2
1
0
Order By: Relevance
“…This is consistent with previous studies 67 which suggest that women are at higher disadvantage in terms of having adverse structural, behavioural and psychosocial characteristics across the lifespan that are related to poor late-life health outcomes. Again, the current finding is similar (for childhood SES) to existing studies which showed that childhood SES was associated with old-age mental health among women but not among men in models fully adjusted with adulthood SES and risk factors 68 , 69 . Considering the interaction results segregated by gender, having a fair childhood health and poor childhood SES had higher odds of cognitive impairment both among men and women in comparison to having a good health and SES in childhood and the odds were greater among women.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with previous studies 67 which suggest that women are at higher disadvantage in terms of having adverse structural, behavioural and psychosocial characteristics across the lifespan that are related to poor late-life health outcomes. Again, the current finding is similar (for childhood SES) to existing studies which showed that childhood SES was associated with old-age mental health among women but not among men in models fully adjusted with adulthood SES and risk factors 68 , 69 . Considering the interaction results segregated by gender, having a fair childhood health and poor childhood SES had higher odds of cognitive impairment both among men and women in comparison to having a good health and SES in childhood and the odds were greater among women.…”
Section: Discussionsupporting
confidence: 89%
“…This study found that adult socioeconomic status can mediate the relationship between childhood socioeconomic status and depression level in older adults, which is supported by studies by Arx et al [ 49 ] and Angelini et al [ 50 ]. Early life environment can have a long-term impact on one's future decisions [ 51 ], and socioeconomic status has a certain degree of stability and heritability [ 52 ], so that childhood socioeconomic status can influence adult socioeconomic status,and higher socioeconomic status usually means better income, better social security and support, and even better health conditions, among other factors, all of which help to promote mental health and reduce depression level.…”
Section: Discussionsupporting
confidence: 88%
“…These results were expected since previous literature has robustly demonstrated how demographic, socio-economic, and health-related factors are related to depressive symptoms. For example, older age, being a woman, having a higher body mass index, a disadvantaged socioeconomic status, chronic conditions, and weaker cognitive functioning have been related to an increased number of depressive symptoms (Kessler and Bromet, 2013;Fukukawa et al, 2004;Cheval et al, 2021;von Arx et al, 2019;Richardson et al, 2015;Nouwen et al, 2010;Pruchno et al, 2016;Aichele et al, 2018a;Aichele et al, 2018b;De Wit et al, 2009;Noh et al, 2015). Crucially, the independent and interactive associations between poor sleep quality and physical inactivity with depressive symptoms were only slightly attenuated after adjustment for those factors.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%